Factors associated with medication adherence among type 2 Diabetes patients in a private clinic in Yangon, Myanmar - Wai Yan Maung Maung (2017)
This cross-sectional quantitative research was designed to determine the proportion of adherence to oral hypoglycemic agents (OHAs) and to explore factors associated with medication adherence among type 2 diabetes patients in a private clinic in Yangon, Myanmar. A total of 396 type 2 diabetes patients were face to face interviewed between April and May 2016. Chi-square test and multiple logistic regression were used to analyze the data. More than half (65.9%) of the patients were reported as good adherence to oral-hypoglycemic agents. The result showed that significant predictors associated with medication adherence included household income, number of under 12 children, knowledge on diabetes, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, family support and cues to action. In multiple logistic regression, significant predictors associated with adherence to oral hypoglycemic agents (OHAs) include high level of diabetes knowledge (Adj OR = 3.55, 95% CI = 1.89 – 6.66), positive perceived susceptibility to diabetes complications (Adj OR = 2.08, 95% CI = 1.08 – 4.00), positive perceived severity of diabetes mellitus (Adj OR = 2.54, 95% CI = 1.30 – 4.93), positive perception on barriers (Adj OR = 2.73, 95% CI = 1.50 – 4.97) and high level of self-efficacy (Adj OR = 4.14, 95% CI = 1.99 – 8.61). The result of this study indicated that health education and health promotion programs should be promoted in order to expand the knowledge of diabetes and life-style modifications.